2008
DOI: 10.1098/rsif.2008.0166
|View full text |Cite
|
Sign up to set email alerts
|

A simple modification of the Hodgkin and Huxley equations explains type 3 excitability in squid giant axons

Abstract: The Hodgkin and Huxley (HH) model predicts sustained repetitive firing of nerve action potentials for a suprathreshold depolarizing current pulse for as long as the pulse is applied (type 2 excitability). Squid giant axons, the preparation for which the model was intended, fire only once at the beginning of the pulse (type 3 behaviour). This discrepancy between the theory and experiments can be removed by modifying a single parameter in the HH equations for the K + current as determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 39 publications
4
55
0
Order By: Relevance
“…In some experiments the squid giant axons had type 3 instead of type 2 excitability [16,17]. The discrepancy between the type 2 behavior of the HH model and experiment was explained by modifying a single parameter in the term describing the potassium current [18]. In a recent study of the periodically stimulated HH model by the present author it was found that the ring rate may be either continuous or discontinuous function of the current amplitude, depending on the stimulus frequency [19].…”
Section: Introductionmentioning
confidence: 99%
“…In some experiments the squid giant axons had type 3 instead of type 2 excitability [16,17]. The discrepancy between the type 2 behavior of the HH model and experiment was explained by modifying a single parameter in the term describing the potassium current [18]. In a recent study of the periodically stimulated HH model by the present author it was found that the ring rate may be either continuous or discontinuous function of the current amplitude, depending on the stimulus frequency [19].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Paydarfar, Forger and Clay (2006) showed that small oscillatory stimuli can be used to induce a state transition in a bistable system. While, we could theoretically model the Hodgkin-Huxley model as a bistable system by adding a sufficiently large exogenous depolarizing persistent current, previous studies have shown that the squid axon, which is the basis for the Hodgkin Huxley model, fails to exhibit repetitive firing under the condition of a persistent depolarizing current clamp (Clay, Paydarfar, & Forger 2008). Furthermore, our preliminary analysis suggested that the first-order gradient algorithm does not readily converge because of the sensitivity of the Hodgkin-Huxley system, specifically the terminal point, even to small changes in the stimulus.…”
Section: Methodsmentioning
confidence: 99%
“…Na + currents were as described above using the PC kinetic scheme (Eq. (4)); K + and leakage currents were as per HH (respective maximal conductances: 36 and 0.3 mS/cm 2 ; respective equilibrium potentials: −72 and −49.4 mV, [36]; cf., [12,48]). Ionic concentrations were assumed to remain constant (cf., [60,65]); channel densities were assumed to be uniformly distributed with no clustering over the axonal surface area (cf.…”
Section: Numerical Analysis and Axonal Cablementioning
confidence: 96%